An ultra-dense linkage map identified quantitative trait loci corresponding to fruit quality- and size-related traits in red goji berry - Rehman, Fazal; Gong, Haiguang; Ma, Yun; Zeng, Shaohua; Ke, Danmin; Yang, Chao; Zhao, Yuling; Wang, Ying (Frontiers in Plant Science, 2024)
Goji berries are a small-fruited shrub with industrial importance whose fruit considered beneficial in both fresh and dried forms. Current germplasms of goji berries include small fruits with a short shelf life, less sweet and bitter taste, and lack of appropriate genetic information. Whole genome resequencing was employed to generate an ultra-dense bin linkage map of the goji berry, which spanned a total length of 966.42 cM and an average bin interval of 0.03 cM. Subsequent variant calling and ordering resulted in 3,058 bins containing 35,331 polymorphic markers across the 12 chromosomes. Human sensory tests were carried out to determine the bitter taste (BT) and sweet taste (ST), and quantification of soluble solid content (SSC), fruit firmness (FF), and fruit size-related traits of fresh goji fruits over three or four years. To elucidate the genetic basis of goji fruit quality and size/weight, quantitative trait loci (QTL) mapping analysis was performed in a cross-pollinated hybrid interspecific population. A total of 99 QTLs, with individual loci in different environments explaining a phenotypic variance of 1.21-16.95% were identified for the studied traits. Ten major effects, including colocalized QTLs corresponding to different traits, were identified on chromosomes 1, 3, 5, 6, 7, and 8, with a maximum Logarithm of Odds (LOD) of 29.25 and 16.95% of explained phenotypic variance (PVE). In addition, four stable loci, one for FF, one for fruit weight (FW), and two for fruit shape index (FSI), were mainly mapped on chromosomes 5, 6, and 7, elucidating 2.10-16.95% PVE. These findings provide valuable insights into the genetic architecture of goji fruit traits along with identified loci and markers to further improve and develop sweet and larger fruited goji berry cultivars with longer shelf-life.